2011
DOI: 10.1088/0029-5515/51/6/063033
|View full text |Cite
|
Sign up to set email alerts
|

Objectives, physics requirements and conceptual design of an ECRH system for JET

Abstract: A study has been conducted to evaluate the feasibility of installing an ECRH system on the JET tokamak. This paper presents an overview of the studies performed in this framework by an EU-Russia project team. The motivations for this major upgrade of the JET heating systems and the required functions are discussed. The main results of the study are summarised. The usefulness of a 10MW level EC system for JET is definitely confirmed by the physics studies. Neither feasibility issues nor strong limitations for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…With the aim of analysing whether the inclusion of more off-axis current could lead to a steady-state scenario, the inclusion of an ECRH/ECCD system, consistent with the proposed configuration for JET [23], is considered. Here, the ECRH/ECCD power used is P EC = 10 MW (170 GHz, X-mode, 2nd harmonic), with two launching mirrors (5 MW each) located at major radius R = 4.32 m and height With this configuration, the deposition is located at ρ ∼ 0.6 as shown in figure 13.…”
Section: Analysis Of the Impact Of Off-axis Current On Shot 77895mentioning
confidence: 99%
“…With the aim of analysing whether the inclusion of more off-axis current could lead to a steady-state scenario, the inclusion of an ECRH/ECCD system, consistent with the proposed configuration for JET [23], is considered. Here, the ECRH/ECCD power used is P EC = 10 MW (170 GHz, X-mode, 2nd harmonic), with two launching mirrors (5 MW each) located at major radius R = 4.32 m and height With this configuration, the deposition is located at ρ ∼ 0.6 as shown in figure 13.…”
Section: Analysis Of the Impact Of Off-axis Current On Shot 77895mentioning
confidence: 99%
“…The latter two are based on recent quotations provided by companies expert in the field whereas the mirror cost is taken from W7-X [36] rescaled with dimensions. The cost estimation per meter as a function of L, r = 1.75w + 90 mm normalized to the EWGs cost for 2009 ECRH4JET project [37,38] is <0.6 for L > 2 m. After ~8 m the cost reaches a lower saturation (<0.4) because the reduction of number of mirrors is counterbalanced by the mirror size increase. The increase for a larger radius (r = 2w + 90 mm) is ~10-15%.…”
Section: Transmission Line (Tl)mentioning
confidence: 99%
“…The principal goals of an ECRH system on JET are: current drive over a range of radii for NTM stabilization, sawtooth control and current profile tailoring and central electron heating to equilibrate electron and ion temperatures in high performance discharges and additionally to avoid W accumulation. The feasibility study [10] concluded that a 12 gyrotron, 10 MW, system at the ITER frequency (170 GHz) adapted for fields of 2.7-3.3 T would be appropriate for the planned operation in JET. It is proposed to use the ITER upper launcher steering mechanism to allow for toroidal and poloidal steering over a wide range.…”
Section: Electron Cyclotron Resonance Heatingmentioning
confidence: 99%
“…It consists in using offaxis ECCD to produce a significant change of the q-profile [10]. The simulation of an existing JET discharge (#77895 at n e0 * 5.5 10 19 m -3 , I p = 1.7 MA) where ECRH power has been added, have shown that 10 MW are sufficient for a local inversion of the q-profile at mid-radius and for fully non-inductive conditions (V loop = 0) corresponding to an ECRH driven current of *200 kA [11].…”
Section: Impact Of Dt At Jetmentioning
confidence: 99%